TEMPORAL LOBE EPILEPSY PRESENTING AS DEPRESSION AND NON SPECIFIC PSYCHOTIC SYMPTOMS — A CASE REPORT - Teeluckdharry, Sadira Sastra; Kaler, Rupinder Jit; Jainer, Ashok Kumar; Sultana, Mahnoor (Journal of Pakistan Psychiatric Society, 2007)
We report on a 36 years old male who developed symptoms of depression and non specific psychotic symptoms. The initial diagnosis was considered depression with psychosis. However, clouding of consciousness and fluctuation in symptoms led us to investigate an organic explanation for the presentation. Collateral history revealed past history of epilepsy and EEG report indicated temporal lobe epilepsy. His symptoms were well controlled with Carbamazepine. This report suggests that temporal lobe epilepsy should be considered as the differential diagnosis when patients frequently present with non specific psychotic symptoms, depressive symptoms fluctuations in symptoms and conscious levels. Key words: Temporal Lobe Epilepsy, Depression, Psychotic Symptoms.